Analysis of Guidance and Counseling Planning in Modern Islamic Boarding Schools in Medan City - Abdurrahman; Yose Rizal; Saiful Akhyar; Amiruddin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the planning of guidance and counseling programs in Modern Islamic Boarding Schools (Pesantren) in Medan City. Using a qualitative case study approach, research was conducted in three pesantren: Ar-Raudhatul Hasanah, Al-Kautsar Al-Akbar, and Ta’dib al-Syakirin. Data were collected through observations, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model and Saldana’s method. Findings reveal that guidance and counseling planning in modern pesantren is systematic and involves multiple stakeholders, including psychologists. Each pesantren follows core planning principles, such as identifying student needs, analyzing school conditions, setting objectives, designing programs, and optimizing resources. Ar-Raudhatul Hasanah uses problem checklists and tabulation analysis, structuring plans from annual to daily levels. Al-Kautsar Al-Akbar conducts academic surveys and collaborates with dormitory teachers to set flexible goals. Ta’dib al-Syakirin emphasizes goal clarification, prioritization, and documentation for continuous development. Despite differences in needs assessment and implementation strategies, all three pesantren recognize structured planning as vital for effective program execution. With systematic planning and regular evaluations, guidance and counseling services become more responsive, enhancing students’ academic and personal development.